Maturity-associated variation in functional characteristics of elite youth tennis players - Myburgh, G. K.; Cumming, S. P.; Silva, M. C. E.; Cooke, K.; Malina, R. M. (Pediatric Exercise Science, 2016)
Purpose: To evaluate relationships among skeletal maturity, body size, and functional capacities of elite junior tennis players. Methods: Participants were 88 elite British Junior tennis players (44 male; 44 female), 8-16 years of age (12.4+-1.9 years). Skeletal age estimated maturty. Anthropometry, grip strength, countermovement jump, squat jump, forehand agility, backhand agility, Yo-Yo, 5-m, 10-m and 20-m sprints were measured. Comparative analysis for each sex was performed, relating advanced maturers (Male: 15; Female: 29) to a combination of on-time and late maturers (Male: 29; Female: 31). ANCOVAs were used to determine absolute differences between male and female players and between the 2 maturity subgroups, with chronological age as the covariate. Results: Advanced maturity afforded male players advantages in absolute measures of grip strength, speed, upper and lower body power but not in acceleration, agility or aerobic endurance. Male players were significantly taller than females in the U13-U16 age group. Advanced maturity in female players afforded advantages in absolute measures of grip strength, agility and overhead power, but not in backhand agility, aerobic endurance or squat jump power. Conclusion: It is important that talent identification protocols consider the maturity of youth athletes to more satisfactorily address athletic potential rather than transient physical capabilities.